Microbial degradation and decolorization of AZO and anthraquinone textile dyes. - PRATISTHA DWIVEDI; RAJESH SINGH TOMAR (International Journal of Pharma and Bio Sciences, 2017)
Azo dyes constitute the largest and most versatile class of synthetic dyes used in the textile industries and represent major components in wastewater from these industrial dying processes. Biological decolorization of azo dyes occurs efficiently and provides an eco-friendly option for remediation. In this study, we describe the use of Bacillus sp., isolated from a discharge effluent of a textile industry, for the sequential decolorization and detoxification of the azo dyes; Acid red, Remazol black, and anthraquinone dye; Reactive blue. This strain was put on the observation for its efficiency to decolorize all three dyes for the period of 96 hrs. It was shown to exhibit almost complete decolorization of all three dyes (1000 mgl-1) within period of study. For optimized colour removal, the most suitable pH and temperature were pH 5.0-7.0 and 35°C, respectively. The isolate was able to decolorize all the dyes tested more efficiently in presence of carbon source - glucose and nitrogen source – peptone, as revealed by performing experimentation on various carbon and nitrogen sources. To explore the maximum tolerance of the bacterial strain towards dyes, high concentration of all three dyes in the range of 1000 to 5000 mgl-1 was tested. The bacterial consortium of mixed culture was found to be more efficient and could completely decolorize dyes in 48 hrs of incubation. The results reported here warrant further investigation to establish the application of the isolate for bioremediation and biodegradation at industrial scale for waste water treatment.